Pengaruh Perubahan Iklim Terhadap Konsumsi Listrik Rumah Tangga Provinsi Banten - Muhamad Fakhrudin; Ahmad Fatoni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to examine the effect of climate change on household electricity consumption in Banten Province. The research uses a quantitative method of panel data from 4 districts and 4 cities in Banten Province during 2016 to 2020. Three indicators are used to see climate change, namely air temperature, solar radiation and rainfall. The results showed that partially air temperature had a significant positive effect on household electricity consumption, solar radiation had a positive effect on household electricity consumption, and rainfall had a significant positive effect on household electricity consumption. Simultaneously these three variables have an influence on household electricity consumption in Banten Province.